2020
DOI: 10.1002/jper.20-0458
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mucosal phenotype on marginal bone levels around tissue level implants: A prospective controlled trial

Abstract: Background The aim of this 1‐year prospective clinical trial was to compare clinical parameters and marginal bone levels (MBLs) around tissue level implants with a partially smooth collar between patients with thin (≤2 mm) and thick (>2 mm) vertical mucosal phenotypes. Methods Thirty patients needing a single dental implant were recruited and allocated to thin (n = 14) or thick (n = 16) phenotype groups. Post‐restoration, clinical (probing depth, recession, width of keratinized mucosa, bleeding on probing, sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 37 publications
(55 reference statements)
2
21
0
Order By: Relevance
“…The same should be considered true for distal bone which is typically thicker than mesial bone 41,42 . Importantly, this study population was also made up of the same cohort of a randomized clinical trial involving implant placement in the edentulous site adjacent to two teeth (which were included in the present study) 28 . To control for KM as a confounder in the mentioned cohort, presence of ≥ 2 mm of KM was considered in the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same should be considered true for distal bone which is typically thicker than mesial bone 41,42 . Importantly, this study population was also made up of the same cohort of a randomized clinical trial involving implant placement in the edentulous site adjacent to two teeth (which were included in the present study) 28 . To control for KM as a confounder in the mentioned cohort, presence of ≥ 2 mm of KM was considered in the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…This clinical study was designed as a single arm prospective clinical trial. A total of 26 patients from a cohort undergoing implant placement in the posterior area were recruited 28 . Implants were placed in premolar or molar position at identical proportion ( n = 13/13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We must mention though that most of our implants were above the red lines established for those important variables: (1) more than 2 mm of keratinized tissue, (2) more than 2 mm of tissue thickness and (3) more than 1 mm of buccal bone to implant (Table 1 and Figure 6). In any case, the influence of these parameters is being questioned in more recent studies, particularly that related to the thickness of the tissue [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…A recent NMA supports the view that thick supracrestal tissue can provide significantly less marginal bone loss [ 12 ]. A subsequent clinical trial by Garaicoa-Pazmino found that by providing more space for the formation of the supracrestal gingiva through tissue level implants, the marginal bone loss difference between gingival phenotypes could be mitigated to the level of non-significance at 1-year follow-up [ 13 ]. However, the influence of various alveolar ridge preservation (ARP) techniques on soft tissue outcomes remains to be determined [ 3 ].…”
Section: Introductionmentioning
confidence: 99%